Chemopreventive, apoptotic, antiangiogenic efficacy of Hesperidin via mitigation of epigenetic alterations of global DNA methylation and targeting microRNA in a rat model of hepatocellular carcinoma - Al-semelawy, A’laa E.; Hussein, Samy A.; Ali, Hussein A.; EL-Senosi, Yakout A.; Abdel Magid, Afaf D.; Mostafa, Shawky A. (Journal of Advanced Veterinary Research, 2024)
Hepatocellular carcinoma (HCC) accounting about 75% of hepatic neoplasia, making it the most common kind of liver cancer worldwide. So, this study was planned to evaluate the beneficial chemopreventive efficacy of hesperidin (Hes) in experimental model of Diethyl nitrosamine (DEN) / Carbon tetrachloride (CCl4) â€“induced HCC in rats. Thirty male rats were divided into 3 equal groups. Group 1 (normal control): rats didn’t receive any treatment. Group 2 (HCC): HCC was induced in rats by injection of DEN (200mg/kg b.w/i.p), then 2 weeks later of DEN injection rats received 3 weekly successive doses of CCl4 (3ml/kg b.wt/ orally) at 1:1 dilution in corn oil as a promoter of carcinogenic effect. DEN and CCl4 administration were repeated once again after 5 weeks. Group 3 (HCC+ hesperidin): 15 weeks after HCC induction, rats treated with Hes (150 mg/kg b.wt), orally and continued for 6 weeks. A significant increase in serum ALT, AST and ALP activities were observed in HCC-induced rats.Â However, significant downregulation of liver Nrf2, Caspase-3, Bcl-2 and MicroRNA-34a with upregulation of FGF-2 and MicroRNA-221 with Global DNA hyper-methylation were observed in HCC group. Hesperidin treatment exhibited downregulation of microRNA-221 and FGF-2 with upregulation of Nrf2, Bcl-2, caspase 3 gene and Global DNA hypo-methylation. Interestingly, improvement of liver histopathological alterations supported the chemopreventive activity of Hesperidin. Conclusively, Hesperidin ameliorates the progression of HCC and has promising chemopreventive, and antiangiogenic activity, inhibiting growth promoting oncogene and initiation of gene regulating apoptosis and protects the liver from oxidative damage and inflammation.